Evaluation of an NADPH-dependent assay for inhibition screening of Salmonella enterica DOXP Reguctoisomerase for identification of novel drug hit compounds - Ngcongco, Khanyisile (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2020)
Invasive non-typhoidal Salmonella, caused by the intracellular pathogen Salmonella enterica, has emerged as a major cause of bloodstream infections. It remains a neglected infection responsible for many deaths in Africa, as it fails to receive the level of support that is given to most better known infections. There are currently no vaccines against invasive non-typhoidal Salmonella. First-line antibiotics have been used for treatment, however, the rise in the resistance of the bacteria against these antibiotics has made treatment of invasive salmonellosis into a clinical problem. Therefore, the discovery of new compounds for the development of antibiotic drugs is required. Central metabolic pathways can be a useful source for identifying drug targets and among these is the non-mevalonate pathway, one of the pathways used for the biosynthesis of isoprenoid precursors. The second step of the non-mevalonate pathway involves the NADPH-dependent reduction of 1-deoxy-D-xylulose 5-phosphate (DOXP) into 2-C-methyl-D-erythritol 4-phosphate (MEP). 1-Deoxy-D-xylulose 5-phosphate (DOXP) reductoisomerase plays a vital role in the catalysis of this reaction and requires NADPH and divalent metal cations as co-factors for its activity. In this investigation recombinant DOXP reductoisomerase from Salmonella enterica, Plasmodium falciparum and Mycobacterium tuberculosis were biochemically characterized as potential targets for developing drugs that could be used as treatment of the disease. The expression and nickel-chelate affinity purification of S. enterica DOXP reductoisomerase in a fully functional native state was successfully achieved. However, the expression and purification of P. falciparum DXR and M. tuberculosis DXR was unsuccessful due to the formation of insoluble inclusion bodies. Although alternative purification strategies were explored, including dialysis and slow dilution, these proteins remained insoluble, making their functional analysis not possible. An NADPH-dependent enzyme assay was used to determine the activity of S. enterica DXR. This assay monitors the reduction of DOXP to MEP by measuring the absorbance at 340 nm, which reflects the concentration of NADPH. An alternative assay, resazurin reduction, which monitors the NADPH-dependent reduction of resazurin to resorufin, was explored for detecting enzyme activity. The recombinant S. enterica DOXP reductoisomerase had a specific activity of 0.126 Â± 0.0014 Î¼mol/min/mg protein and a Km and Vmax of 881 Î¼M and 0.249 Î¼mol/min/mg respectively. FR900098, a derivative of fosmidomycin, is a well-known inhibitor of DXR, however, the sensitivity of S. enterica DXR towards FR900098 has not yet been reported. The NADPH dependent enzyme and resazurin reduction assays were used to determine whether FR900098 has enzyme inhibitory effects against S. enterica DXR. Upon confirming that FR900098 is able to inhibit S. enterica DXR, FR900098 was used as a control compound in the screening of novel compounds. The S. enterica DXR enzyme was screened for inhibition by the collection of compounds from the Pathogen Box. Compounds that exhibited the desired inhibitory activity, referred to as 'hits' were selected for further investigation. These hits were confirmed using the NADPH-dependent enzyme assay, resulting in the identification of two different DXR inhibitor compounds, MMV002816, also known as diethylcarbamazine, and MMV228911. The inhibitory concentration (IC50) values of FR900098, MMV002816 and MMV228911 against S. enterica DXR were 1.038 Î¼M, 2.173 Î¼M and 6.861 Î¼M respectively. The binding mode of these compounds to S. enterica DXR could lead to the discovery of novel druggable sites on the enzyme and stimulate the development of new antibiotics that can be used for treating Salmonella infections.
Keywords: 1-Deoxy-D-xylulose 5-phosphate; Antibiotics; Drug development; Salmonella; Enterobacteriaceae; Vaccines; Plasmodium falciparum; Mycobacterium tuberculosis